Pengembangan Media Pembelajaran Senam Aerobik “Fun Young” Pada Materi Senam Irama Di SMP Negeri 1 Suwawa Timur - Pakaya, Sahrul; Ruslan, Ruslan; Datau, Suriyadi (-, 2025)
This study aims to develop learning media for Aerobic Fun Young gymnastics for rhythmic gymnastics subjects at SMP Negeri 1 Suwawa Timur. Using the Research and Development (RD) approach with the ADDIE model framework (Analysis, Design, Development, Implementation, Evaluation), this study produces an innovative and integrated learning media package. This package consists of a guidebook and learning videos that are designed interactively, combining elements of music, and movement visualization. The data collection process involved interviews with teachers and students, direct observation and distributing questionnaires to measure the effectiveness and practicality of the media. The results of validation by three experts, namely (gymnastics experts, learning experts and multi-media experts) showed an average score above 4, indicating that this learning media is very suitable for use to support the rhythmic gymnastics learning process in schools. It is expected that this learning media can improve students' understanding and skills in rhythmic gymnastics and provide a more enjoyable and effective learning experience.